Analyzing Social Media Strategy in Korean Music Industries - Ni Wayan Liana Mega Putri; Dianiangriani Dilia (PERSPEKTIF, 2023)
The Korean Wave (K-wave), also known as Hallyu, is the term used to describe the phenomenon of Korean pop culture, including TV dramas, movies, pop music, fashion, and online games, becoming widely popular and shared among the people of Japan, China, Hong Kong, Taiwan, and other Asian nations. Korean pop music, also known as K-pop, became a major component of the second K-wave after the first K-wave's drama-focused craze. Additionally, K-pop's fanbase has grown outside of Asia to the West thanks to the quick adoption of social media platforms like YouTube and Twitter. The popularity of K-pop throughout the world helps to improve the perception of "Korea" and has a positive effect on the Korean economy. According to reports, Korea has 1,000 active entertainment agencies in addition to the "big three" record labels and agencies: SM Entertainment, YG Entertainment, and JYP Entertainment. In this instance, we talk about the K-pop phenomenon's global appeal and how social media has contributed to the genre's recent boom. Our lessons on how to manage social media strategically, with a focus on the major agencies mentioned above, include: aligning your strategic business model with social media; maximizing different social media channels; enticing customers with on- and offline promotions; and stimulating audience with exclusive content.